AN ANALYSIS OF A 1.6 YEAR OLD BOYS’ LANGUAGE ACQUISITION PROCESS (A CASE STUDY ON BILINGUAL FAMILY) - Sartika Dewi Harahap Sartika Dewi Harahap (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
In this case, the writer presents how the child (a boy) acquires the language. The natural process of language acquisition takes place since birth. This study will focus on language acquisition process of a 1.6 year old boy who becomes the object of the observation. In a fact, human language skills can be improved through two ways, namely acquisition and learning. The methodology of this research is descriptive qualitative approach. The techniques of collecting data used are documentation and observation. The objectives of descriptive qualitative study are obtained from the utterances of a 1.6 year old boy, his name is Fati. On the discussion part the analysis will focus on syntax, vocabulary and the factors that affect him in acquiring language. As the object, the boy is obtained four languages as simultaneous languages, namely Indonesian, English, Mandailingnese and Javanese. In conclusion, the object of this case is able to produce words and phrases based on he usually heard